Analisis Manajemen Resiko Pada UMKM “Es Boba Lima Warna” - Wijaya, Noval (Universitas Serambi Mekkah, 2024)
The Lima Warna Boba business was established with the aim of meeting public demand for the currently popular boba drink. Boba is a tapioca ball that is often used as a filling in bubble tea drinks. To achieve its vision and mission, Lima Warna Boba requires the right strategy to increase sales and compete with other boba drink manufacturers that have already entered the market. The purpose of this study is to analyze the strategies used by Lima Warna Boba in increasing sales through the use of modern technology. The research method used is a qualitative method with interview and observation techniques. The data sources used are primary data and secondary data. The final result of the study is that there are several strategies used during the running of the